Effects of surface roughness and processing parameters on heat transfer coefficient between polymer and cavity wall during injection molding. Issue 5 (May 2016) - Liu, Yao; Gehde, Michael
Abstract Injection molding is one of the most commonly applied processing methods for plastic components. Heat transfer coefficient (HTC), which describes the heat conducting ability of the interface between a polymer and cavity wall, significantly influences the temperature distribution of a polymer and mold during plastic component injection molding. This study focuses on HTC under diverse processing situations. On the basis of the heat conducting principle, a theoretical model for calculating the average HTC within an injection cycle was presented. Experimental injection studies were also performed to acquire necessary temperature data. The heat quantity and HTC across the interface between a polymer and cavity wall was on the basis of the results of the experimental injection studies. The factors influencing the HTC were analyzed on the basis of the factor weight during injection molding cycle. Finally, the surface roughness of plastic components obtained from disparate processing situations was measured and compared with the surface roughness of inserts. The surface roughness results are in good agreement with the HTC value and can be used to interpret the cause of variation. The results of this study will be beneficial for understanding the heat transfer process comprehensively, predicting the temperature field, arranging the cooling system, and offering precise HTC for numerical simulation.